Identifikasi Keanekaragaman Polen Tanaman Sumber Pakan Lebah pada Madu Lokal dari 5 Desa di Kabupaten Boyolali - Nurul Hidayati; Sri Widodo Agung Suedy; Sri Darmanti (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2020)
Honey is a natural sugar produced by bees from the nectar of plants or secretions of living parts of plants or excrtions of plant sucking insects on the living parts of plants. Pollen is an important component contained in honey, as a source of protein for bees. The This study aims to determine the diversity of pollen which is a source of bee feed, and knowing the type of honey based on the type and frequency of pollen in honey in 5 villages in Boyolali Regency. The method used for the pollen analysis is acetolysis. The quantitative data of pollen analysis using Excel Software. The results showed the diversity of plant pollen in honey from 5 village in Boyolali is 52 taxa, and the type of honey based on the frequency and types of pollen varies, the village Cerme and Cepogo honey is multifloral honey, Kiringan and Pager Village honey including monofloral honey, and Kemiri Village honey is bifloral honey.